1989
DOI: 10.1295/polymj.21.829
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Properties, and Crosslinking Studies on Polyurethane Elastomers

Abstract: ABSTRACT:Polyurethane elastomers were prepared from structurally distinct hydroxyterminated polybutadiene and polyether-ester based prepolymers with diisocyanates such as hexamethylenediisocyanate, toluenediisocyanate, and diphenylmethanediisocyanate by the one short polymerizatiQn process. The effect of crosslinking by polyfunctional alcohols such as castor oil, trimethylolpropane, and poly(vinyl alcohol) on mechanical properties is compared in case of hydroxyterminated polybutadiene based polyurethane system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…In these nonstoichiometric samples, the excess isocyanate groups react with urethane groups to form allophanate linkages [2]. Many studies have examined the effects of chemical crosslink on the material properties of PU elastomers such as tensile properties [3][4][5][6][7][8][9][10][11][12], swelling [8][9][10][11][12], thermal degradation [6,11], thermal properties [9][10][11], and morphology [11,12]. The studies showed that an increase of crosslinking density has two opposing effects on structure and properties.…”
Section: Introductionmentioning
confidence: 99%
“…In these nonstoichiometric samples, the excess isocyanate groups react with urethane groups to form allophanate linkages [2]. Many studies have examined the effects of chemical crosslink on the material properties of PU elastomers such as tensile properties [3][4][5][6][7][8][9][10][11][12], swelling [8][9][10][11][12], thermal degradation [6,11], thermal properties [9][10][11], and morphology [11,12]. The studies showed that an increase of crosslinking density has two opposing effects on structure and properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a lot of work has been devoted to the characterization of HTPB. [1][2][3][4][5] The most commonly used reactants for end linking of HTPB prepolymer are di-or polyfunctional isocyanates, and the resultant network has the polyurethane structure. 4 -7 The HTPB prepolymer ideally contains two hydroxyl end groups.…”
Section: Introductionmentioning
confidence: 99%
“…In the end-linking reactions, chain extension and branching can be controlled by adjusting the weight ratio of the two functional reactant to polyfunctional reactants. 4,5,7 Therefore, the primary objective of this study is to determine the thermodynamic solution properties of HTPB in two different solvents; second, to compare the effect of the type of reactive system on the endlinking of HTPB chains; and last, to characterize the network structure of HTPB elastomers by following the swelling, solubility and mechanical measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Kothandaraman [13] compared the PU properties obtained from HMDI, TDI, and MDI. The weakest properties were obtained in the case of HMDIbased PU.…”
Section: General Characteristics Of Polyurethanesmentioning
confidence: 99%